DMF–t index level among school children based on parents socioeconomic status - Krishnan, Sujita Kurup Kutty; Syaefullah, Avip; Susilawati, Sri (Padjadjaran Journal of Dentistry, 2015)
Introduction: Malaysia is situated in the southeast region of the Asian continent. Oral health services became prominent in the 1970s as programs related to oral health care were gradually introduced in schools. Various national epidemiological surveys were done to assess the prevalence of dental caries among children in Malaysia. This study was aimed to find out the DMF-t index level among school children based on their parents’ socioeconomic status by collecting consideration of education level and income of the fathers. Methods: This descriptive research with the survey technique was conducted at SJK (T) Klebang, Chemor, Perak, Malaysia. The DMF-t index of children in SJK (T) Klebang, Chemor, Perak was 0.2. Based on the questionnaire, the majority of fathers in Chemor, Perak were in the upper secondary education level with income ranging from RM 500 – RM 1000. Results: The Malaysian Oral Health Survey on 5-years old children showed that the caries prevalence was 75.5%. The mean of DMF-t was 5.57. An oral epidemiological study showed that 95.4% of 6-years old children in Peninsular Malaysia had carious primary teeth. This figure dropped to 88.6% in 1988, and by 1997 a further reduction to 80.6% was reported. DMF-t index consisted of the total number of Decayed, Missing and Filled teeth as well as a questionnaire on the socioeconomic background of the parents. Conclusion: The DMF-t Index of children in SJK (T) Klebang based on their father’s socioeconomic status is within the range of “Very Low” based on the DMF-t Index Scale.